The War of the Worlds - Francis, Pauline (Evans Brothers Ltd, 2005)
This book tells the story of large metal cylinders that fall to Earth, signalling the beginning of a Martian invasion. The Martians gradually take over London and the surrounding area, causing death and destruction. It seems that no one can stop them$1! =s
Keywords: Juvenile Fiction